Methodology for detecting anomalies in cyber attack assessment data using Random Forest and Gradient Boosting in machine learning - A. S. Kechedzhiev; O. L. Tsvetkova; A. I. Dubrovina (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The research aims to detect anomalies in data using machine learning models, in particular random forest and gradient boosting, to analyze network activity and detect cyberattacks. The research topic is relevant as cyber attacks are becoming increasingly complex and sophisticated. Developing effective methods for detecting anomalies and protecting against cyber threats is becoming a priority for organizations. Method. The research is carried out using two machine learning algorithms: Random Forest and gradient boosting. The process includes analyzing important metrics, visualizing solutions, evaluating the performance of each model, and analyzing error matrices for attack categories. Result. The Random Forest model showed an accuracy of about 94% when using the top 10 important features. The graph provides insight into how the model makes decisions based on features. The Xgboost gradient boosting model achieved high accuracy and reliability of results. The report provides a description of the model's performance for each category. Conclusion. The work done is the result of a comprehensive analysis of a machine learning model designed to detect cyberattacks. It includes several key steps and methods that allow us to evaluate the effectiveness of the model, identify important features, and analyze performance for various attacks.